Konteks Aplikasi Sedar ‘Rumah Pintar’ - Abdul Ghani, Nur Zuraihah (Universiti Sains Malaysia, 2006)
This thesis describes the development of a context aware application for intelligent home. The application is simulated on two desktop personal computer connected through RS232 interface. The RS232 will act as a null modem to allow both computers to communicate with each other. One of the personal computer acts as a sensor whilst the other is act as a display panel. The development uses Visual Basic 6.0 and MSComm Control.